Petrological and strength properties of granite in Johor - Wong, Grace Ming Chia (2012)
The study described in this paper is performed on igneous rock at Bukit Waha, Kota Tinggi, Johor. The texture and mineralogy of the granite and the physical properties of aggregates in terms of strength are assessed. This study aim to investigate and evaluate the influence of petrological of the rock encountered at an existing quarry hill in Bukit Waha to the strength properties of the rock. Petrography was quantified from thin sections with a polarizing microscope to determine the rock texture and grain size distribution. Laboratory works such as Point Load Test, Brazillian Test, and Uniaxial Compressive Strength (UCS) Test were performed in accordance to the International Society for Rock Mechanics (ISRM) to obtain the relevant parameters. Through this study, there will be an understanding on the effect of petrological of the rock material to the strength properties and the correlation between the strength parameters of granite. Results show that there is significant factor between tensile strength and UCS in a ratio of 1 to 10. Meanwhile, for point load index, IS(50) and UCS correlated, the correction factor is 15, within the range of correction factor determined by other researchers.